Ayurveda Management of Bipolar Affective Disorder – A Case Report - Jancy, K S; Jithesh, M (International Research Journal of Ayurveda & Yoga, 2024)
Bipolar affective disorder (BPAD) often refers to as bipolar disorder which characterized by depressive and manic or hypomanic episodes. These disorders include: Bipolar disorder type I and bipolar disorder type II. The prevalence rate is approximately 1% across all populations and is typically treated with mood stabilizers, antipsychotics, and therapy. However, limitations include potential side effects, individual response variations, and the challenge of finding the right medication combination. Ayurvedic treatments are observed as beneficial in bipolar disorders. Few studies are only reported in this condition. The present article deals with a diagnosed case of BPAD, with current episode of depression. The Ayurvedic diagnosis was Kapha-Pittaja unmada and assessments were done before and after treatment, with HAM D Scale. Patient showed improvement in depressed mood, appearance and restlessness. Sodhana and Samana Karma play a key role in the management of BPAD. Ayurvedic treatment helps to stabilize the mood and improves the quality of life in BPAD.